Opinions of cardiologists on class II recommendations in current European Society of Cardiology 2018-2020 guidelines: YELLOW BOX - Kış, Mehmet; Güzel, Tuncay; Ekici, Berkay; Zoghi, Mehdi (The European Research Journal, 2022)
Objectives: We planned our survey study to evaluate the opinion of cardiologists about the class II recommendations on levels of evidence in the current European Society of Cardiology Guidelines (ESC). Our aim is to determine which diagnosis or treatment option most prefer by cardiologist when guidelines do not make clear recommendations. Methods: The survey was conducted on September 2020 with the participation of cardiologists (n = 102). Our survey covers ESC's guidelines published in 2018-2020 on diagnosis and treatment strategies in coronary artery disease, diabetes, heart valve disease, arrhythmia, dyslipidemia and heart failure. Our survey consisting of 40 questions was shared with the cardiologists via e-mail. Results: Participants answered all of the survey questions. The majority of the participants (79.41%) did not consider the addition of a second long-term antithrombotic medication in addition to aspirin for secondary prevention in diabetes mellitus (DM) and coronary artery disease (CAD) patients who are not at high risk of bleeding. The lowest low density lipoprotein (LDL) value achieved by the participant physicians with treatment in their practices was < 40 mg/dl in 32 (31.37%) participants . One of the striking results of the survey was that 51.96% of the participants stated that it was not possible to measure the lipoprotein a (Lp(a)) level in the center where they were carrying out their practices, and 34.31% did not consider the Lp(a) level in the treatment of dyslipidemia in terms of directing the treatment. As for patients with asymptomatic Wolff-Parkinson-White (WPW) syndrome, 58.82% of the participants considered catheter ablation therapy. Conclusions: Although there were different opinions on some recommendations, the participants were mostly in agreement. We think that these survey results, which were mostly based on expert opinions, may contribute to the guidelines to be published in the future with the increase of survey studies on these issues.